Spectrophotometric Estimation of Ceftibuten in Pharmaceutical Formulations - SRINIVASU, K.; VENKATESWARA RAO, J.; APPALA RAJU, N.; MUKKANTI, K. (Asian Journal of Chemistry, 2010)
Three simple, accurate, rapid and sensitive methods (A, B and C) have been developed for the estimation of ceftibuten in its pharmaceutical dosage form. The method A is based on reaction of ceftibuten with ferric chloride and 1,10-phenanthroline to form a blood red coloured chromogen. The method B is based on reaction of ceftibuten with ferric chloride with 2,2'-bipyridyl to form blood red coloured chromogen. These methods exhibit maximum absorption at 510 and 520 nm, respectively and obey the Beer's law in the concentration range of 0.125- 2.5 and 0.065-2.0 mcg/mL respectively. Method C based on reaction of ceftibuten with ferric chloride and potassium ferricyanide produces blue coloured chromogen having a maximum absorbance at 720 nm. The methods have been statistically evaluated and were found to be precise and accurate. The proposed methods are economical and sensitive for the estimation of ceftibuten in bulk drug and in its formulations.